INCLUSIVE EDUCATION READINESS AMONG PRE-SERVICE TEACHERS AT ONE UNIVERSITY IN ASTANA - Bazarbayeva, Guldana (Nazarbayev University Graduate School of Education, 2025)
Despite the efforts to strive for quality teaching in inclusive education, Kazakhstan still faces significant challenges in its journey towards inclusive education. There is a lack of comprehensive understanding of current pre-service teacher training programs in Kazakhstani universities. It is not clear how universities prepare future teachers for inclusive education. This gap may contribute to insufficient teacher readiness and impact the quality of inclusive learning environments. Therefore, this qualitative study aims to explore the experiences of pre-service teachers in learning and practising inclusive education at one Kazakhstani university in Astana. Specifically, the study explores six key questions: (1) pre-service teachers’ understanding and conceptualisation of inclusive education, (2) their perceptions and attitudes toward the inclusive education courses within their teacher education program, (3) their feelings of preparedness or unpreparedness to implement inclusive education and the contributing factors, (4) their practical experiences with inclusive education during pedagogical internships at schools, (5) their perceptions of the alignment between the inclusive education theories presented in coursework and the realities encountered during internships, and (6) the broader implications of their experiences and perceptions for inclusive education policy, teacher education practices, and future research in Kazakhstan. The study adopts a qualitative, phenomenological research design. Data were collected through semi-structured interviews with eight pre-service teachers enrolled in a teacher education program of different subject specialisations. The findings showed a strong understanding of the concept of inclusion among participants. However, their practical readiness varied significantly. The study also revealed that inclusive education courses were overly theoretical and lacked real classroom exposure. Participants highlighted mentorship, emotional readiness, and school-level support as critical factors impacting their level of preparedness. The study recommends revising pre-service teacher training programs to include strong mentorship and emotional support from in-service teachers at school, practice-oriented course content, and greater alignment between theoretical instruction and the real classroom environment.
Keywords: pre-service teachers; teacher preparation; teacher readiness; teacher preparedness; pedagogical practice; Kazakhstan; inclusive education; Type of access: Open